Investigating the effect of intracameral cefuroxime on oxidative stress and apoptosis in the rat cornea - Ozkan,Ufuk (2019)
ABSTRACT PURPOSE: We examined the effect of intracameral administration of cefuroxime on oxidative stress and endothelial apoptosis in rat corneal tissue. METHODS: In total, 30 rats were divided into 3 groups of 10 rats each (intracameral administration of cefuroxime 0.1 mg/0.01 mL (cefuroxime group); intracameral administration of balanced salt solution 0.01 mL (control group); or absence of intracameral injection (sham group). Corneal endothelial apoptosis was assessed by immunohistochemical analysis using caspase-3 and caspase-8. Total oxidant status, total antioxidant status, oxidative stress index, and paraoxonase and arylesterase levels were examined in corneal endothelial tissue and serum. RESULTS: Paraoxonase levels in the serum were significantly different between the sham and cefuroxime groups (p=0.027). A significant difference was also observed in total oxidant status levels between the cefuroxime and balanced salt solution groups (p=0.023). In addition, there were significant differences in total antioxidant status levels in corneal tissue between the cefuroxime and sham groups (p<0.001) and between the cefuroxime and balanced salt solution groups (p<0.001). Furthermore, significant differences were also observed in oxidative stress index levels between the cefuroxime and balanced salt solution groups (p=0.001) and between the cefuroxime and sham groups (p=0.026). According to the immunohistochemical staining results, a significant association with caspase-3 activity existed between the cefuroxime and balanced salt solution groups (p=0.007), while no significant difference was found with caspase-8 activity (p=0.541). Caspase-3 activity exhibited a significant relationship between the sham and balanced salt solution groups (p=0.018), but no relationship was found with caspase-8 activity (p=0.623). CONCLUSION: Immunohistochemical examination revealed that intracameral cefuroxime increased apoptosis when compared to the sham and balanced salt solution groups. Moreover, intracameral cefuroxime increased oxidative stress in the cornea and simultaneously induced apoptosis.